Analisis Pengambilan Keputusan UMKM Sabana Fried Chicken - Dwi Ayu Rossmiharti; Valentino Dwi Herlambang; Ramadiaz Perkasa Sulistya; Diaz Arief Ardiansyah; Ujang Suherman (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the decision-making process in facing various operational constraints at the Sabana Fried Chicken MSME based on field visits and direct interviews with business owners. MSMEs play a strategic role in the Indonesian economy, but in practice, they still face various limitations, both in terms of human resources, capital, raw materials, and marketing. The research method used was a qualitative explanatory survey approach, where data were obtained through direct observation, semi-structured interviews with owners and employees, and documentation of visit activities. The results of the study indicate that decision-making at the Sabana MSME is carried out simply and based on experience, especially in managing a limited workforce, managing business capital that is still independent, raw material procurement that relies on certain suppliers, and marketing strategies that rely on location and affordable prices. These constraints affect the quality of decisions taken, but flexibility and speed in decision-making are advantages for the Sabana MSME in maintaining its business. The conclusion of this study indicates that improving the quality of decision-making can be achieved through more systematic planning and utilization of market information. The implications of this research are expected to provide input for similar MSMEs in managing their businesses more effectively.